DESIGNING SUPPLEMENTARY MATERIALS FOR TEACHING-LEARNING OF WRITING EXPLANATORY TEXT BASED ON A GENRE-BASED APPROACH - Cornelia, Cornelia; Ikhsanudin, Ikhsanudin; Surmiyati, Surmiyati; Apriliaswati, Rahayu; Rezeki, Yanti Sri (Premise: Journal of English Education and Applied Linguistics, 2023)
Writing an explanatory text following the advanced contents in the textbook may be arduous for rural students. Territory differences remarkably denote that students' needs for topics in the explanatory text are also distinct. Therefore, the exposure topics must be by the students' conditions. This study aimed to design supplementary materials as an e-book based on the genre-based approach for students' learning of writing explanatory text with closely-related topics. The students were the eleventh graders of SMAN 01 Seponti at Kayong Utara regency. This study employed research and development (R&D) with the procedure of the ADDIE concept (Analyze, Design, Develop, Implement, Evaluate). The data collection employed instruments, field notes, interview protocol, documenting notes, and questionnaires. We collected the data through observation, interview, document analysis, and questionnaire distribution. The data were analyzed using fieldnote reflection, interview transcription, textbook analysis results, and the rating scale interpretation. The need analysis results show that the textbook used by the teacher to teach writing the explanatory text was not in line with the student's condition. After the e-book was entirely developed, the internal evaluation was inquired. It resulted in the 'very good' category for its general appearance, layout and design, methodology, activities, language skills, language content, topic content, teachability and flexibility, and assessment, with percentages of 93,33%, 93,33%, 93,33%, 86,67%, 93,33%, 93,33%, 93,33%, 86,67%, 80%, respectively. The study implies that the product is feasible, and this study may add insights for future research.